A Cross Sectional Study of Behavior Disorders In 6-15 Years Age Group in Rural Area - Rasote, Kirti C; Gore, Alka D; Ranganathan, Usha (National Journal of Community Medicine, 2015)
Background: Child & adolescent psychiatric disorders and behav- ioral disorders are not given adequate attention. Such studies are either school based or hospital based. Methods: To study the prevalence and pattern of behavior disor- ders among children from the community a cross sectional study was conducted in rural area with 600 children of 6-15 years age group by the ‘Purposive Sampling’ method. Percentages & chi square test was used. Results: Response rate was 94%. Out of 600 children 252(42%) had behavior disorders and majority 155(26%) had at least one behavior disorder. Among these Personality problems (44.84%), eating prob- lems (33.73%), habit problems (23.01%), Scholastic problems (17.46%), sleep problems (11.9%), antisocial problems (11.11%), psychosomatic (7.53%) & speech problems were (2.77%). Only 22% informants of children knew about psychiatric disorders. Conclusions: The prevalence of behavior disorders was found to be high in children, but informants were found to be largely igno- rant about these problems.